2022
DOI: 10.1111/1541-4337.12892
|View full text |Cite
|
Sign up to set email alerts
|

An overview of antimicrobial properties of kombucha

Abstract: Kombucha is a traditional beverage of Manchurian origin, typically made by fermenting sugared black or green tea with the symbiotic consortium of bacteria and yeast (SCOBY). The beverage has gained increasing popularity in recent years, mainly due to its heralded health benefits. The fermentation process of kombucha also results in the production of various bioactive compounds with antimicrobial potential, making it a promising candidate in the exploration of alternative sources of antimicrobial agents, and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 141 publications
0
10
0
Order By: Relevance
“…In the present study, the antibacterial effect of BNC-coated elastomers could be attributed to the bioactive compounds of kombucha used to produce cellulose. Kombucha is a consortium of yeast and bacteria produced by fermenting sugared black or green tea with SCOBY [ 30 , 43 ]. The fermented broth, originating from Manchuria (China), can produce a variety of active compounds with antimicrobial activity against micro-organisms such as S .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the antibacterial effect of BNC-coated elastomers could be attributed to the bioactive compounds of kombucha used to produce cellulose. Kombucha is a consortium of yeast and bacteria produced by fermenting sugared black or green tea with SCOBY [ 30 , 43 ]. The fermented broth, originating from Manchuria (China), can produce a variety of active compounds with antimicrobial activity against micro-organisms such as S .…”
Section: Discussionmentioning
confidence: 99%
“…Various pharmacological studies have demonstrated that kombucha possesses antioxidant, antimicrobial, cytotoxic, anti-inflammatory, and anti-hyperglycemic properties. [5][6][7][8][9] However, scientific data are still needed to compare the bioactivities of unfermented and fermented materials and to understand the chemical dynamics in SCOBY represented by the enzymatic transformation of the chemical components of the raw material and the production of substances important for its survival.…”
Section: Introductionmentioning
confidence: 99%
“…Kombucha tea is a low-alcoholic functional beverage traditionally prepared from the fermentation of sweetened black or green tea by a symbiotic culture of bacteria and yeasts (SCOBY). The original drink is of Asian origin, but nowadays it is globally consumed due to its beneficial health effects, such as anti-microbial and antioxidant effects [1], treatment for gastric ulcers [2] and high cholesterol [3], and liver detoxification [4].…”
Section: Introductionmentioning
confidence: 99%